Identification of obstacles for parabolic problems - Heck, Horst; Ramm, Alexander G. (My University, 2012)
Obstacle identification problems for parabolic equations and systems are considered. Unique continuation property plays an important role in the arguments. These arguments are based on the idea which was first used in the paper MR0847528 (87k:35248) of one of the authors earlier. The technique is applied to inverse problems for slightly compressible fluids and to inverse problems for the heat equation.
Keywords: Inverse problem; Obstacle identification; Parabolic problems